2015
DOI: 10.1007/s12205-015-0635-2
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic behavior of transitions between different railway track typologies

Abstract: A railway track stretch comprising three different track typologies (i.e., ballasted track, asphalt slab track and concrete slab track) has been modeled using a three-dimensional Finite Elements model, which has been calibrated and validated using real acceleration records. In this model, two different analyses have been run: a static analysis to assess the stiffness evolution and a dynamic analysis to calculate the accelerations induced by the train loads along the transition zones. These analyses have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Yu et al (2011), and Leshchinsky and Ling (2013) on the other hand, used linear elastic material formulations only for subgrade. Finally, Real et al (2016) used linear elastic material formulation for granular layers with an additional damping factor obtained from accelerometers in the field. Note that the instrumentation effort during the current study focused on the measurement of wheel loads and the displacements of individual track substructure layers.…”
Section: Materials Formulationmentioning
confidence: 99%
“…Yu et al (2011), and Leshchinsky and Ling (2013) on the other hand, used linear elastic material formulations only for subgrade. Finally, Real et al (2016) used linear elastic material formulation for granular layers with an additional damping factor obtained from accelerometers in the field. Note that the instrumentation effort during the current study focused on the measurement of wheel loads and the displacements of individual track substructure layers.…”
Section: Materials Formulationmentioning
confidence: 99%
“…According to the survey, it was revealed that CBL is appropriate according to lower maintenance requirements and higher availability and the reduction of structure height for high-speed railways such as the Shinkansen in the world [24][25][26]. Using the static and dynamic behavior of three different types of railway in the track area, Real et al showed that the slope of stiffness changes in the transition zone between the slab and ballast tracks decreases by decreasing the stiffness of the rubber around the embedded rail [27]. Moreover, Shuber et al investigated the performance of the railway track system under the harmonic load by the FEM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent decades, research on the dynamic interaction of vehicle-rail bridges has increased and primarily focuses on the following aspects: (1) e dynamic response of trains in dangerous areas, such as road bridge transitions, curved bridges, and culvert transition zones [12][13][14][15][16][17][18][19]. (2) e dynamic performance of a train that passes through a bridge under external adverse influences, such as earthquake, wind and bridge skewness, or noise of composite bridge results [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%